Gender Beneath the Skull: Agency, Trauma and Persisting Stereotypes in Neuroepigenetics - Lawson-Boyd, Elsher; Meloni, Maurizio (Frontiers in Human Neuroscience, 2021)
Epigenetics stands in a complex relationship to issues of sex and gender. As a scientific field, it has been heavily criticized for disproportionately targeting the maternal body and reproducing deterministic views of biological sex (Kenny & Muller 2017; Lappe 2018; Richardson et al 2014). And yet, it also represents the culmination of a long tradition of engaging with developmental biology as a feminist cause, because of the dispersal of the supposed ‘master code’ of DNA among wider cellular, organismic and ecological contexts (Keller 1988; Malabou 2016). In this paper, we explore a number of tensions at the intersection of sex, gender and trauma that are playing out in the emerging area of neuroepigenetics - a relatively new subfield of epigenetics specifically interested in environment-brain relations through epigenetic modifications in neurons. Using qualitative interviews with leading scientists, we explore how trauma is conceptualised in neuroepigenetics, paying attention to its gendered dimensions. We address a number of concerns raised by feminist STS researchers in regard to epigenetics, and illustrate why we believe close engagement with neuroepigenetic claims, and neuroepigenetic researchers themselves, is a crucial step for social scientists interested in questions of embodiment and trauma. We argue this for three reasons: 1) Neuroepigenetic studies are recognising the agential capacities of biological materials such as genes, neurotransmitters and methyl groups, and how they influence memory formation; 2) Neuroepigenetic conceptions of trauma are yet to be robustly coupled with social and anthropological theories of violence (Eliot, 2021; Nelson, 2021; Walby, 2013); 3) In spite of the gendered assumptions we find in neuroepigenetics, there are fruitful spaces – through collaboration – to be conceptualising gender beyond culture-biology and nature-nurture binaries (Lock and Nguyen, 2010). To borrow Gravlee’s (2009: 51) phrase, we find reason for social scientists to consider how gender is not only constructed, but how it may “become biology” via epigenetic and other biological pathways. Ultimately, we argue that a robust epigenetic methodology is one which values the integrity of expertise outside its own field, and can have an open, not empty mind to cross-disciplinary dialog.